2004
DOI: 10.1254/jphs.fp0040098
|View full text |Cite
|
Sign up to set email alerts
|

Effects of NSAIDs on Bladder Function in Normal and Cystitis Rats: a Comparison Study of Aspirin, Indomethacin, and Ketoprofen

Abstract: Abstract. To clarify the potential usefulness of non-steroidal anti-inflammatory drugs, NSAIDs, for patients with overactive bladder, we examined the effect of NSAIDs on urodynamic parameters in normal and cystitis rats and compared their ulcerogenic activity in the gastrointestinal mucosa. Cystometry was performed after administration of the conventional NSAIDs, aspirin, indomethacin, or ketoprofen. Prostaglandin levels were measured in the bladder of cystitis rats pretreated with NSAIDs. Furthermore, the ulc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
38
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 24 publications
1
38
0
2
Order By: Relevance
“…Aspirin, indomethacin or ketoprofen prolonged IC in the bladder infl ammation (22). The present study demonstrated that loxoprofen prolonged IC during the acetic acid infusion.…”
Section: Discussionsupporting
confidence: 60%
“…Aspirin, indomethacin or ketoprofen prolonged IC in the bladder infl ammation (22). The present study demonstrated that loxoprofen prolonged IC during the acetic acid infusion.…”
Section: Discussionsupporting
confidence: 60%
“…Tricyclic antidepressants, such as amitriptyline, may increase bladder capacity through β-adrenoceptors on the bladder and inhibition of the hypersensitivity of the bladder sensory nerves by blocking reuptake of noradrenalin and serotonin, as well as anticholinergic and antihistaminic effects (7,50,51). The anti-inflammatory effect of NSAIDs, such as indomethacin, helps to reduce the hypersensitivity of the bladder sensory nerves (52,53), although the anti-inflammatory effect on the bladder inflammation, which was indicated by increased bladder weight and induction of TNF-α mRNA expression, was not observed in the present administration schedule. A potent opioid analgesic, morphine, may be used for severe bladder pain and referred pain in IC patients (34), while it suppresses urinary frequency through spinal and supraspinal mechanisms by acting on μ-opioid receptors (54,55).…”
Section: Discussionmentioning
confidence: 99%
“…Many published reports have proposed models of bladder inflammation (3,8,17,21,29,32). Acetic acid (AA) infusion into the urinary bladder of rats shortened inter-contraction interval (ICI) in cystometrograms (20,28).…”
mentioning
confidence: 99%
“…Cyclooxygenase synthesizes PGs from arachidonic acid, whereas non-steroidal anti-inflammatory drugs (NSAIDs) are known to inhibit cyclooxygenase. Because NSAIDs have been shown to prolong ICI, it is possible that they would inhibit afferent nerve activity during AA-induced inflammation (28,29). PGE 2 receptors are classified into four subtypes during the interval between distensions.…”
mentioning
confidence: 99%